Effect of compression on coir industry waste material. (2022) - Neethi Manickam, I.; Logesh, K.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: The densification of agricultural residues is influenced by both physical characteristics and process factors. The densification mechanism gave better results. The agriculture residue is treated and reused for attaining the sustainable environment. The influence of humidity and pressure on the coir pith briquettes' relaxed density was investigated in this study. When the moisture content and pressure measured are 278.16 bar and 18 percent respectively and 716.48 kg/m3 is the relaxed density and also the relaxation is minimal.